2014
DOI: 10.1108/ijrdm-07-2012-0065
|View full text |Cite
|
Sign up to set email alerts
|

Young consumers' innovativeness and hedonic/utilitarian cool attitudes

Abstract: Purpose – This study aims to investigate the relationship between young consumers' innovativeness and their hedonic/utilitarian attitudes toward cool clothing and to examine the moderating role of income on this relationship. This study uses five cool factors (singular cool, personal cool, aesthetic cool, functional cool and quality cool) under the hedonic and utilitarian cool dimensions to test the hypotheses. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 36 publications
1
22
1
1
Order By: Relevance
“…Sproles (1979) applied the diffusion of innovation theory in the context of fashion. Because not every consumer purchases the latest fashion products or newest styles before their commercial introduction in the marketplace, fashion adoption follows a path similar to that of diffusion of innovation (Noh et al 2014). Sproles (1979) confirmed the role of innovativeness and fashion opinion leadership in the adoption of a new fashion.…”
Section: The Effects Of Innate Innovativeness On Fashion Leadership Amentioning
confidence: 99%
“…Sproles (1979) applied the diffusion of innovation theory in the context of fashion. Because not every consumer purchases the latest fashion products or newest styles before their commercial introduction in the marketplace, fashion adoption follows a path similar to that of diffusion of innovation (Noh et al 2014). Sproles (1979) confirmed the role of innovativeness and fashion opinion leadership in the adoption of a new fashion.…”
Section: The Effects Of Innate Innovativeness On Fashion Leadership Amentioning
confidence: 99%
“…For example, in the context of information technologies, innovativeness was illustrated as a major moderator between salient perceptions (ease of use, usefulness) and usage intentions (Agarwal & Prasad, 1998). Noh et al (2014) explored the attitudes and innovativeness of young consumers toward newly released products. Results suggested that innovative consumers with a high income have more desire to buy new cool products rather than old-fashioned consumers.…”
Section: Conceptual Model and Research Hypothesesmentioning
confidence: 99%
“…Several other studies suggest that less educated consumers tend to have higher score on ethnocentrism. Although in some cases, young consumers are innovative and seek more hedonic value ( Noh et al, 2014 ), in both developed and developing countries they hold similar degrees of ethnocentrism.…”
Section: Socio-psychological Factorsmentioning
confidence: 99%